2015
DOI: 10.1016/j.devcel.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynein-Based Accumulation of Membranes Regulates Nuclear Expansion in Xenopus laevis Egg Extracts

Abstract: Nuclear size changes dynamically during development and has long been observed to correlate with the space surrounding the nucleus, as well as with the volume of the cell. Here we combine an in vitro cell-free system of Xenopus laevis egg extract with microfluidic devices to systematically analyze the effect of spatial constraints. The speed of nuclear expansion depended on the available space surrounding the nucleus up to a threshold volume in the nanoliter range, herein referred to as the nuclear domain. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 51 publications
16
83
0
Order By: Relevance
“…Similar scaling relationships have been reported for the mitotic spindle (Good et al, 2013) and centrosome (Decker et al, 2011), suggesting that cytoplasmic volume may be a universal regulator of organelle growth (Goehring and Hyman, 2012). Hara and Merten (2015) also identified molecular factors, including the amount of membrane and the levels of the motor protein dynein, that contribute to the rate of nucleus expansion. Inhibition of microtubule assembly or dynein activity restricted the growth of nuclei both in test tubes and while encapsulated in microfabricated channels.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Similar scaling relationships have been reported for the mitotic spindle (Good et al, 2013) and centrosome (Decker et al, 2011), suggesting that cytoplasmic volume may be a universal regulator of organelle growth (Goehring and Hyman, 2012). Hara and Merten (2015) also identified molecular factors, including the amount of membrane and the levels of the motor protein dynein, that contribute to the rate of nucleus expansion. Inhibition of microtubule assembly or dynein activity restricted the growth of nuclei both in test tubes and while encapsulated in microfabricated channels.…”
supporting
confidence: 59%
“…For example, do changes in nucleus size directly alter transcription or the spatial organization of the genome? Given that an altered nucleocytoplasmic ratio is linked to cellular senescence and cancer, in vitro studies like this one by Hara and Merten (2015) may provide paradigms for understanding size control relevant to both healthy and diseased cells. Growth is dependent on the amount of locally accessible cytoplasm.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This interpretation was subsequently rejected on the grounds that the LISs are unfeasibly large, and the cells of later developmental stages are smaller, too small to contain the same amount of genetic material . However, given cell size, the nuclei are not unfeasibly large, or even unusually large for palintomically dividing cells (Huldtgren et al, 2012), and analyses have demonstrated an isometric relationship between cell and nucleus volume in living eukaryotes, like the one that we observe (Cavalier-Smith, 2005;Conklin, 1912;Goehring and Hyman, 2012;Kimura, 2009, 2011;Hara and Merten, 2015;Jorgensen et al, 2007;Neumann and Nurse, 2007;Tsichlaki and FitzHarris, 2016;Wilson, 1925). Furthermore, in living eukaryote systems, within a few rounds of palintomy, cell volume does indeed diminish to less than the original volume of the nucleus (Tsichlaki and FitzHarris, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when X. laevis egg extract was treated with a dynein inhibitor prior to encapsulation in the microchannels, nuclear expansion was greatly inhibited, implicating a microtubuleand dynein-based mechanism of nuclear size regulation. 137 Other new technologies allow for measuring the entire transcriptomes of individual cells, by coupling microfluidic encapsulation of individual cells with next generation sequencing. 138 For example, whereas only 5 mouse retinal cell types were previously known, this so-called Drop-seq method identified 39 distinct cell types based on individual cell profiles.…”
Section: New Technologies To Study Nuclear Size Regulationmentioning
confidence: 99%